Peran Kepala Sekolah Sebagai Administrator Dalam Meningkatkan Kinerja Sekolah (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
A school principal can be defined as a teacher functional staff who are given the task of leading a school where the teaching and learning process is held and managing educational units. Administrator can be interpreted as the entire work process between two or more people who are tasked with taking care of matters related to administration. Meanwhile, school performance is essentially the productivity of the performance of all school residents and is an indicator of the quality of education, because the failure of school performance is part of the failure of the principal. This study aims to describe the role of the principal as an administrator in improving school performance which focuses on the principal's management functions. This research uses a qualitative approach. The method used is descriptive. The data collection technique is carried out in three ways, namely (1) interviews, (2) observations, and (3) documentation. The collected data is analyzed descriptively, through the flow of (1) data reduction, (2) data presentation, (3) conclusion drawn. The validity of the data is carried out by triangulation of respondents, methods and times. From the field findings, it was found as follows: (1) Educational management planning is carried out at the beginning of the school year through school work meeting activities attended by school steakholders, (2) The implementation of school activities is in accordance with the school program that has been prepared, (3) Evaluation/supervision is carried out periodically by the principal through a supervision program, (4) Follow-up is carried out based on the results of evaluation by carrying out improvements and standardization of activities schools that have been achieved. In the implementation of these four activities, the principal found several obstacles faced. However, solutions were also found to solve the problems or obstacles found, so that school activities ran smoothly.